Directional in the Balinese language - I Ketut Artawa, Ida Ayu Agung Ekasriadi, (Opción, 2019)
This article aims to investigate directional in the Balinese language via the reflective-introspective method. The analysis of data was done applying the distributional method. As a result, apart from the adjective beneng/menang, the preposition used to express direction in the Balinese language is the preposition ka ‘to’ and uli/uling ‘from’. In conclusion, semantically in the Balinese language directional is used based on five variables; they are the mount-sea pivot, points of the compass, the agent’s goal, and the agent’s physical position/object of the sentence